Co‐Encapsulation of EGCG and Quercetin in Liposomes for Optimum Antioxidant Activity. Issue 1 (12th December 2018) - Chen, Weijun; Zou, Mingming; Ma, Xiaobin; Lv, Ruiling; Ding, Tian; Liu, Donghong
Abstract: Although different delivery systems have been developed to overcome the limits of Epigallocatechin‐3‐gallate (EGCG) and quercetin in food application, none have referred to their simultaneous encapsulation. In this study, these two polyphenols were successfully co‐loaded into liposomes. Under the optimal conditions (lecithin‐total polyphenols ratio 25:1, lecithin‐cholesterol ratio 6:1, lecithin‐Tween 80 ratio 8:1 and ultrasonic time 2 min), the mean size, polydispersity index (PDI) and zeta potential of liposomes were 111.10 ± 0.52 nm, 0.259 ± 0.006 and –19.83 ± 0.45 mV, with an encapsulation efficiency of 64.05 ± 1.56% and 61.73 ± 2.55% for EGCG and quercetin, respectively. After 30‐day storage, an increase of 4.05% was observed in the mean size with no significant change ( P ≥ 0.05) in the PDI and zeta potential. Moreover, 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) assay revealed a synergistic antioxidant effect of the two compounds in liposomal system. These results demonstrated that co‐encapsulation of EGCG and quercetin enhances their effectiveness. Practical Application: EGCG and quercetin are natural polyphenols abound in the human diet with diverse biological activities. These two polyphenols were successfully co‐encapsulated into a homogeneous and stable liposomal system. Interestingly, a synergistic antioxidant effect of the two polyphenols was observed due to co‐encapsulation. This indicated that the simultaneous delivery of EGCG and quercetin was an attractive approach to improve their functionality for expanding their application in food, cosmetic and pharmaceutical industries.